2018
DOI: 10.4274/uob.978
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients Who Underwent Ureterocutaneostomy

Abstract: Objective: Ureterocutaneostomy (UCS) is a urinary diversion (UD) method which is used rarely in a carefully selected patient group. In this study, we aimed to present the data and long-term outcomes of patients who underwent UCS treatment in our clinic. Materials and Methods: A total of 36 patients who underwent UCS between January 2000 and December 2017 were included in the study. All patients had unilateral or bilateral ureteral-skin anastomosis. The demographic data, diagnoses, comorbidities, side of UCS (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Acute pyelonephritis was diagnosed in eight patients (22.22%) postoperatively, although all patients were found to have a positive culture in urine collected from their nephrostomy tube. This incidence is in accordance with the reported in the literature for uretero-cutaneostomy and transuretero-cutaneostomy (2.27%-42.30%) [24][25][26][27]. In six patients, acute pyelonephritis resulted from complications related to the nephrostomy tube (dislocation in three, obstruction and hydronephrosis in two, and post-replacement pyelonephritis in one).…”
Section: Discussionsupporting
confidence: 90%
“…Acute pyelonephritis was diagnosed in eight patients (22.22%) postoperatively, although all patients were found to have a positive culture in urine collected from their nephrostomy tube. This incidence is in accordance with the reported in the literature for uretero-cutaneostomy and transuretero-cutaneostomy (2.27%-42.30%) [24][25][26][27]. In six patients, acute pyelonephritis resulted from complications related to the nephrostomy tube (dislocation in three, obstruction and hydronephrosis in two, and post-replacement pyelonephritis in one).…”
Section: Discussionsupporting
confidence: 90%
“…In 1852, Simon first described the urinary diversion procedure and Bricker in 1950 popularized the ileal conduit (IC) technique [5]. Since then, this procedure has become popular among surgeons and is considered the first option for urinary diversion procedures [6]. Meanwhile, Johnston described uretero-cutaneostomy in 1963 for a patient with congenital urinary obstruction [7].…”
mentioning
confidence: 99%
“…Additionally, an IC procedure requires an intestinal segment as a urinary diversion, while uretero-cutaneostomy can avoid the complications associated with bowel anastomosis [6]. However, several studies have shown this procedure has a high incidence of ascending infection and stoma stenosis [6,9]. Meanwhile, both procedures showed the same result concerning the patients' quality of life [10].…”
mentioning
confidence: 99%
“…Rectal resection and termino-terminal sigmorectal anastomosis and a preventive colostomy were performed due to the suspected rectal infiltration and absence of surgical cleavage plane from the cervix. Because of the ileal resection, ileal conduit urinary diversion according to the Bricker technique was contraindicated; therefore, we opted for a left ureterocutaneostomy [ 4 , 5 ]. In addition, the right ureter showed neoplastic infiltration in the inferior third, and therefore, we removed the infiltrated tissue and closed the ureter (as the patient had already undergone a right nephrostomy).…”
Section: Case Reportmentioning
confidence: 99%